π-Conjugated Polymer Nanoparticles from Design, Synthesis to Biomedical Applications: Sensing, Imaging, and Therapy - Nada Elgiddawy; Noha Elnagar; Hafsa Korri-Youssoufi; Abderrahim Yassar (Microorganisms, 2023)
In the past decade, π-conjugated polymer nanoparticles (CPNs) have been considered as promising nanomaterials for biomedical applications, and are widely used as probe materials for bioimaging and drug delivery. Due to their distinctive photophysical and physicochemical characteristics, good compatibility, and ease of functionalization, CPNs are gaining popularity and being used in more and more cutting-edge biomedical sectors. Common synthetic techniques can be used to synthesize CPNs with adjustable particle size and dispersion. More importantly, the recent development of CPNs for sensing and imaging applications has rendered them as a promising device for use in healthcare. This review provides a synopsis of the preparation and functionalization of CPNs and summarizes the recent advancements of CPNs for biomedical applications. In particular, we discuss their major role in bioimaging, therapeutics, fluorescence, and electrochemical sensing. As a conclusion, we highlight the challenges and future perspectives of biomedical applications of CPNs.